2021
DOI: 10.21203/rs.3.rs-569029/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic Significance of the Albumin-to-globulin Ratio for Advanced Urothelial Carcinoma Treated with Pembrolizumab: A Multicenter Retrospective Study

Abstract: Although the albumin-to-globulin ratio (AGR) is a promising biomarker, no study has investigated its prognostic significance for advanced urothelial carcinoma (UC). This study conformed to the REporting recommendations for tumor MARKer prognostic studies (REMARK) criteria. We retrospectively reviewed 176 patients with advanced UC treated with pembrolizumab between 2018 and 2020. We evaluated the associations between pretreatment clinicopathological variables, including the AGR and performance status (PS), with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 19 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…Regarding the prognostic factors, poor performance status (ECOG PS ≥ 1) and liver metastasis were shown to be independent predictors of shorter CSS and OS (Tables 3, 4), in this study. These two factors have been reported as critical prognostic factors for patients with aUC [16][17][18], even in the era of immune checkpoint inhibitors [18]. Our results were similar to findings in the previous literature.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the prognostic factors, poor performance status (ECOG PS ≥ 1) and liver metastasis were shown to be independent predictors of shorter CSS and OS (Tables 3, 4), in this study. These two factors have been reported as critical prognostic factors for patients with aUC [16][17][18], even in the era of immune checkpoint inhibitors [18]. Our results were similar to findings in the previous literature.…”
Section: Discussionsupporting
confidence: 92%
“…These two factors have been recognized as strong prognostic markers for aUC, and their utility has been maintained in the pembrolizumab era (note: liver metastasis was previously included in visceral metastasis along with lung and bone metastases, but it has been handled separately in recent years). [1][2][3][4][5][6][7][8][9][10][11][14][15][16][17][18][19][20] Conversely, resection of the primary site was associated with survival in analyses of the entire cohort (Table 2; Table S2) and a subgroup analysis of patients who did not receive pembrolizumab (Table S6), whereas it had no correlation with survival in a subgroup analysis of patients who used pembrolizumab (Table S4). This might be attributable to the functional mechanism of immune checkpoint inhibitors such as pembrolizumab, the responders to which could benefit irrespective of the residual tumor burden, thus negating the cytoreductive effect of resection of the primary site.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CSS (25 months) and OS (24 months) among patients in the recent era cohort who received pembrolizumab were more than 2-fold longer than in patients in the earlier era cohort (CSS and OS: 11 months, Figure 3). Since pembrolizumab was launched as a second-line therapy for aUC in 2017, several studies have reported its outcomes in the real-world setting, [14][15][16][17][18][19][20] and all but one study conducted survival analyses from the start of pembrolizumab therapy. [15][16][17][18][19][20] The remaining study, by Narita et al, performed survival analyses from the start of first-line chemotherapy to compare outcomes between pembrolizumab and conventional chemotherapy as later-line therapies for aUC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations